From Secretion in Pichia pastoris to Application in Apple Juice Processing: Exo-Polygalacturonase from Sporothrix schenckii 1099-18 - Karataş, Ersin; Tülek, Ahmet; Çakar, Mehmet M.; Tamtürk, Faruk; Aktaş, Fatih; Binay, Barış (Protein and Peptide Letters, 2021)
Background: Polygalacturonases are a group of enzymes under pectinolytic enzymes related to enzymes that hydrolyse pectic substances. Polygalacturonases have been used in various industrial applications such as fruit juice clarification, retting of plant fibers, wastewater treatment drinks fermentation, and oil extraction. Objectives: The study was evaluated at the heterologous expression, purification, biochemical characterization, computational modeling, and performance in apple juice clarification of a new exo-polygalacturonase from Sporothrix schenckii 1099-18 (SsExo-PG) in Pichia pastoris. Methods: Recombinant DNA technology was used in this study. Two different pPIC9K plasmids were constructed with native signal sequence-ssexo-pg and alpha signal sequence-ssexo-pg separately. Protein expression and purification performed after plasmids transformed into the Pichia pastoris. Biochemical and structural analyses were performed by using pure SsExo-PG. Results: The purification of SsExo-PG was achieved using a Ni-NTA chromatography system. The enzyme was found to have a molecular mass of approximately 52 kDa. SsExo-PG presented as stable at a wide range of temperature and pH values, and to be more storage stable than other commercial pectinolytic enzyme mixtures. Structural analysis revealed that the catalytic residues of SsExo- PG are somewhat similar to other Exo-PGs. The KM and kcat values for the degradation of polygalacturonic acid (PGA) by the purified enzyme were found to be 0.5868 μM and 179 s-1, respectively. Cu2+ was found to enhance SsExo-PG activity while Ag2+ and Fe2+ almost completely inhibited enzyme activity. The enzyme reduced turbidity up to 80% thus enhanced the clarification of apple juice. SsExo-PG showed promising performance when compared with other commercial pectinolytic enzyme mixtures. Conclusion: The clarification potential of SsExo-PG was revealed by comparing it with commercial pectinolytic enzymes. The following parameters of the process of apple juice clarification processes showed that SsExo-PG is highly stable and has a novel performance.
Keywords: apple juice clarification